أسباب المفردات الفقهية عند أئمة المذاهب - Hasanulddin, Mohd; Omar Ahmed, Ahmed Moqbel Mareai (2018)
Many followers do not understand the disagreement and differences in opinion amongst Islamic jurists. Adequate explanation regarding the various motives for jurisprudential vocabulary by Imams of the schools of Islamic jurisprudence could provide followers with useful information. This study aims to provide detailed explanation about the rationale behind jurisprudential vocabulary in order to increase understanding of religion. The study focuses on religious texts and how to deal with issues whose rules are not established. The researcher used inductive and comparative methods to gather and analyze these motives. One of the most important findings of this study is that the motives for jurisprudential vocabulary constitute a collection of processes involved in every disagreement amongst the scholars. These motives can be summed up into several key points: First, regarding the narration and knowledge about the texts; second, pertaining to the competence in terms of understanding and knowledge of its requirements; third, regarding what it does or does not incorporate of issues whose rules are not established; and fourth: a person working on Ijtihad (juristic deduction) must strive to produce valid evidence, and such person is excused for any mistake and rewarded for Ijtihad. A situation whereby the person who has not been informed of the Hadith or considers it inaccurate in a ruling and based the jurisprudence on a Shar'ia evidence is considered closest to the truth. This is because realizing the truth in all rulings is impossible. The differences in opinion amongst the scholars are neither on the basics of religion nor at the core of Shariah, but only differences in the understanding of certain religious texts and their application.